Patient selection and outcome in low-grade glioma surgery - Jensdottir, Margret; Solheim, Ole; Corell, Alba; de Dios, Eddie; Dunås, Tora; Fletcher-Sandersjöö, Alexander; Gulati, Sasha; Holmgren, Klas; Latini, Francesco; Mahesparan, Ruby; Milos, Peter; Neimantaite, Alice; et al. (Frontiers in Oncology, 2025)
Background and objectivesMaximal safe resection is the cornerstone of diffuse low-grade glioma (dLGG) management, although epidemiological data are limited. We aim to explore surgical selection, techniques, and outcomes in a population-based cohort.Materials and methodsThis study utilized a multi-center case series (9 out of 10 neurosurgical departments in Norway and Sweden) of all adults (≥18 years) with histopathologically verified supratentorial dLGG, WHO grade 2, undergoing primary surgery from 2012-2017. Complications within 30 days and neurological outcomes at 3 months were assessed. Pre- and postoperative MRIs were reviewed centrally, blinded to patient outcome and center.ResultsOf 517 included patients, 217 (41.7%) were female, and the mean (SD) age was 44.5 (15.0) years. Biopsy only was performed in 119 (23.0%) patients (13.8-38.9% across centers), and 398 (77.0%) underwent resection (61.1-86.2%). Intraoperative neurophysiological monitoring (IONM) was used in 142 (35.7%, 0-58.7%) resections. The biopsy-only patients were older (52.7 years vs. 42.1 years, P<.001), had larger tumors (56.6 ml vs. 31.9 ml, P<.001), and these tumors were more often eloquently located (86.6% vs. 56.5%, P<.001). The median (IQR) extent of resection (EOR) was 82.9% (63.3-97.7%), 69.7-100.0% across centers. The median (IQR) residual tumor was 4.6 ml (0.5-19.9 ml), 0.0-14.1 ml across centers. Age and histopathology were the most important predictors of EOR. New/worsened neurological deficits occurred in 165 patients (41.5%), 23.1-66.7% across centers, and persisted in 19 (4.8%, 0-22.7%) at 3 months after surgery. A complication was observed in 87 patients (21.4%, 0-31.7%), with 12 patients (3.1%, 0-9.8%) having grade III-IV complications.ConclusionsWe found that surgical selection was associated with age, tumor size, and location. The median EOR in a population-based cohort was 83%, with age and tumor biology being significant predictors. EOR did not correlate with higher risks or worse neurological outcomes. We provide an epidemiological perspective demonstrating a variation in surgical selection and techniques reflecting persistent controversy in dLGG management.